Cancer treatment data available in European cancer registries: Where are we and where are we going? - Giusti, Francesco; Martos, Carmen; Trama, Annalisa; Bettio, Manola; Sanvisens, Arantza; Audisio, Riccardo; Arndt, Volker; Francisci, Silvia; Dochez, Carine; Ribes, Josepa; Fernández, Laura Pareja; Gavin, Anna; et al. (Frontiers in Oncology, 2023)
Population-based cancer registries are responsible for collecting incidence and survival data on all reportable neoplasms within a defined geographical area. During the last decades, the role of cancer registries has evolved beyond monitoring epidemiological indicators, as they are expanding their activities to studies on cancer aetiology, prevention, and quality of care. This expansion relies also on the collection of additional clinical data, such as stage at diagnosis and cancer treatment. While the collection of data on stage, according to international reference classification, is consolidated almost everywhere, data collection on treatment is still very heterogeneous in Europe. This article combines data from a literature review and conference proceedings together with data from 125 European cancer registries contributing to the 2015 ENCR-JRC data call to provide an overview of the status of using and reporting treatment data in population-based cancer registries. The literature review shows that there is an increase in published data on cancer treatment by population-based cancer registries over the years. In addition, the review indicates that treatment data are most often collected for breast cancer, the most frequent cancer in women in Europe, followed by colorectal, prostate and lung cancers, which are also more common. Treatment data are increasingly being reported by cancer registries, though further improvements are required to ensure their complete and harmonised collection. Sufficient financial and human resources are needed to collect and analyse treatment data. Clear registration guidelines are to be made available to increase the availability of real-world treatment data in a harmonised way across Europe.